Cultivation of Tilapia (Oreochromis Niloticus) In Aquaponic System With Different Plants Species - Simanullang, Diana Rifka; Patang, Patang; Indrayani, Indrayani (Journal of Agroscience Indonesia, 2023)
This study aims to analyze the effect of using different plant species on the growth and survival of tilapia in the aquaponic system and to identify the most effective plant species in maintaining water quality in tilapia rearing with aquaponic systems. This study is an experimental study with a completely randomized design (CRD) with four treatments (the use of kale, lettuce, pakcoy and control without plants) with three replications. The variables observed were the growth and survival of fish during maintenance. The data collected was then analyzed by the ANOVA test. The results showed that there was no significant effect (p>0.05) between the use of different types of plants on the growth of tilapia but the treatment using water spinach gave the highest weight gain for tilapia reaching 2.21g with an absolute length increase of 1.14 cm, and the specific growth rate reached 7.36% per day. The use of different plant species had no significant effect (p<0.05) on the survival of tilapia in the aquaponics system and kale was the most effective plant species in maintaining the water quality performance of tilapia during maintenance.